COMPARATIVE CHARACTERISTICS OF MICE VAGINAL DYSBIOS MODELS, CAUSED BY INTRODUCING OF STRAINS OF STAPHYLOCOCCUS AUREUS - Vorobey, E.S.; Voronkova, O.S.; Vinnikov, A.I. (World of Medicine and Biology, 2016)
Comparative analysis of qualitative and quantitative composition of microflora of the mice’s vagina showed that more significant changes were defined under the dysbiosis, caused by filmforming strain of S. aureus (DFS) comparative to dysbiosis caused by non-filmforming strain of S. aureus (DNS). Thus, under the DFS amount of microaerophilic lactobacilli decreased to 1.07±0.58 lg CFU/ml and frequency of detection was 44.1%, while DNS – 1.71±1.10 lg CFU/ml with the frequency of detection 70.1%. The amount of anaerobic lactobacilli in first group decreased to 3.60±2.46 lg CFU/ml and frequency of detection 44.1% and in second group 3.77±2.28 lg CFU/ml at a frequency of 49.3%, respectively. The amount of staphylococci in model with DFS increased to 3.36±2.36 lg CFU/ml, while DNS – to 2.99±1.38 lg CFU/ml with the frequency of detection 100% in both cases, while the amount of Enterobacteriaceae increased to 2.39±1.30 lg CFU/ml with the frequency of detection 19.1% and to 2.00±1.14 lg CFU/ml and the frequency 19.4% respectively. Besides them, an increase of total microbial amount to 2.79×105 CFU/ml for DFS models and to 1.62×105 CFU/ml – for DNS took place, and the ratio of aerobic to anaerobic bacteria were 1:83 and 1:90 respectively. Thus, DFS characterized by a significant increase of the number of opportunistic and anaerobic bacteria and prolonged stability of dysbiosis.